Is there a Red Sea linguistic area? - (:unkn) unknown (My University, 2006)
In spite of a very long common cultural and linguistic history, the review of the criterion usually used to identify an Ethiopian linguistic area has shown that the Red Sea zone cannot be considered as a linguistic area, in the strict sense of the term. It cannot be denied that deep influences and upheavals took place, but in an unbalanced way. It seems that the Red Sea has been and still is a real borderline for linguistic change in the Arabian Peninsula but not in Africa: major changes, such as language shift, or more minor ones are all due to linguistic contact between the two coasts of the Red Sea; but they occurred in Africa, not in Arabia. From a linguistic viewpoint, Africa received much from Arabia, but the reverse is not true. Thus the Red Sea zone is more accurately defined as a case of asymmetric dominance relations between languages with large-scale shifts, to use the terms of Thomason and Kaufman (1988: 95). But such a conclusion is only partial because it does not account for what happened and is still happening on the west coast. As a matter of fact it seems that, on the African side, influences between Cushitic and Semitic have been and probably still are bidirectional, and that all linguistic levels are affected.
Keywords: African Research